APLIKASI SMART CARD PADA METERAN AIR DIGITAL PRABAYAR BERBASIS ARDUINO MEGA 2560 - Rafik, Adhila; Yuniarto, Yuniarto (Gema Teknologi, 2014)
Adhila Rafik, Yuniarto, in paper smart card application in prepaid digital water meter based on arduino mega 2560 Â explain that water is a daily necessity, to get a decent clean water to be used, we can use the services of the service taps to get water, but the post-pay payment method used taps raises its own problems, namely the problem of payment arrears. To resolve the issue of payment methods can be converted to a prepaid system, so the use of water dilakuakn after the user makes a payment in advance, many prepaid methods, one of which is the smart card is a plastic card in which there is a microcontroller chip that makes it possible to encrypt the data that there didalamya so not just anyone can read and menulisa data into the card, the use of smart cards as a payment method for a digital prepaid water meter taps, can overcome the problem of payment arrears. Because the use of RFID technology allows the User just close the smart card reader to its user. Keywords: smart cards, prepaid, RFID